PERBEDAAN HASIL BELAJAR IPS EKONOMI MENGGUNAKAN PENDEKATAN RECIPROCAL TEACHING DENGAN KONVENSIONAL SISWA KELAS VII SMP NEGERI 20 PADANG - Landini Putri, Elsa; Dewita Hia, Yulna; Sumarni, Sumarni (Pendidikan Ekonomi, 2014)
ABSTRACT This research was motivated by the low economy class student learning outcomes SMP N 20 Champaign Academic Year 2013/2014. This is caused by the lack of activity of students in the learning process. This study aims to determine the differences in learning outcomes of students with the application of economic models Reciprocal Teaching learning with conventional learning on SMP Seventh Grade 20 Padang. This research is an experimental study. The study population was a class VII student of SMP N 20 Champaign school year 2013/2014. Samples were taken by purposive sampling technique, was selected as the class VII6 VII7 experimental class and the class as a control class. The instrument used is the observation sheet achievement test. Data analysis techniques to test the hypothesis is to test Z. Based on the analysis of data obtained an average value of 80.73 experimental class and control class average of 73.37. The results of data analysis known Z count value is greater than 2.091 price 1.960 Z table which means the hypothesis is accepted at significance level α = 0.05. It can be concluded that the learning outcomes of students with the application of economic models Reciprocal Teaching learning better than economics student learning outcomes in the conventional learning process in class VII SMP N 20 Padang. To the principal, especially economic studies teachers are expected to implement the learning model Reciprocal Teaching to improve student learning outcomes. Students are also expected to be more motivated and more active in the learning economy if this strategy is applied. For other researchers who are interested in using learning model Reciprocal Teaching please apply with variations of different tests, different yng school and different subjects.